PROXY WARS IN CYBERSPACE - Torres Soriano, Manuel Ricardo (Journal of the Spanish Institute for Strategic Studies, 2018)
This article proposes an in-depth study into the specific dynamics of cyberspace as a stage onto which to project so-called “proxy wars”. Its basic thesis is that the main advantage which this strategy provides (low risk of retaliation by the actor under attack) is also its principal weakness, since indirect participation in a cyber conflict detracts from a State’s efficiency in reaching tactical objectives, and is of only moderate value for advancing towards the achievement of strategic objectives. Throughout the paper, analysis is made of the advantages and limitations of this strategy, and a typology of the various cyber proxies is proposed based on their relation to the State utilizing them.